Analysis of Chatbot Response Constancy Using Boyer Moore Algorithm - Aldis Gandi Mitra Sanjung; Norhikmah M.Kom (SCOPUS ID: 57216417658) (Sistemasi: Jurnal Sistem Informasi, 2022)
Amikom Computer Club or commonly referred to by the name AMCC is one of the scientific student activity units at Amikom University Yogyakarta. AMCC consists of administrators and members. As the number of AMCC members increases every year, the administrators have difficulty in providing services in answering member questions quickly according to members' needs through the telegram sample chat application. Therefore, a Chatbot system is needed that is built to assist administrators in answering various questions from members using the Boyer Moore Algorithm, by the way the algorithm works that moves to compare characters from right to left or called string matching, thus shortening the information search time. The results of this study are that the chatbot system can respond well to member questions, and the results are tested using the User Acceptence Test, the chatbot only fails to answer 4 questions out of a total of 50 questions, and gets 70% accuracy by testing using the confusion matrix method. AMCC